Validation of the Portuguese version of the Fertility Adjustment Scale - Romeiro, Joana (2022)
There is an urgent need to provide healthcare professionals and midwives with validated tools as to improve fertility adjustment and promote well-being of couples with infertility. The purpose of this study was to test validity of the Fertility Adjustment Scale among people undergoing assisted reproductive techniques. A cross-sectional and methodological study was conducted, and a total of 104 Portuguese adults undergoing fertility treatment were recruited through fertility-related websites. The Fertility Adjustment Scale was administered along with the Spiritual Well-Being Questionnaire and the Resilience Scale for adults as a measure of concurrent validity. Scores revealed the sample’s lack of adjustment to fertility. A significant correlation with measures of resilience provided evidence of convergent validity. There was a significant association of fertility adjustment with time of consultation and the cause of infertility. A Fertility Adjustment Scale with six items is a reliable tool that offers early recognition of patients’ difficulties in adaptation to fertility problems during assisted reproductive techniques, which could be beneficial in not only an early recognition of healthcare intervention but of a more individualized approach to such patients.